Evaluation of Interdisciplinary Readings: M.Ed. First Semester Course Using CIPP Model (Journal of Vishwa Adarsha College, 2025)
This study evaluates the M.Ed. First semester course ‘Interdisciplinary Readings’ offered by Tribhuvan University using Stufflebeam’s CIPP evaluation model (1971). The study was carried out using a qualitative research design. We collected the information through semi-structured interviews with four participants who were selected using the purposive sampling method. Among them, two were the lecturers who taught the course, and two were the students who completed it at a constituent campus of Tribhuvan University in Dang District, Lumbini Province, Nepal. We asked interview questions based on the CIPP evaluation checklist (2002) on the context, input, process, and product, the four elements of the CIPP model. Each interview lasted for approximately one hour. We strictly followed the ethical guidelines, including obtaining informed consent from all participants, ensuring confidentiality and anonymity, and allowing voluntary participation and withdrawal at any point without consequence. The result indicates that the course has realistic objectives. Similarly, the study also reveals that the course demands effort, interaction, and active participation from students as a part of the learning process. However, irregular class attendance among students hinders the intended objectives of the course. Although the course advocated student-centered approaches and methods, the teachers could not come out of stereotypical teaching pedagogy, which brought a sort of disappointment regarding the course implementation and its outcome. Therefore, the study highlights the value of applying the CIPP model for program evaluation, offering insights for improvement and future planning.